Characterization of Exon and Intron of Defensin 1 Gene in Apis cerana and Apis dorsata - Alfiyan, Achmad; Raffiudin, Rika; Astuti, Rika Indri (UI Scholars Hub, 2019)
Honey bee defensin 1 gene belongs to the class of immunity genes in this social insect. The peptide acts as a defensive mechanism against infections caused by Gram-positive bacteria. The aim of this study was to characterize exon 2, intron 2, and exon 3 of defensin 1 gene in both the Indonesian honey bees Apis cerana and A. dorsata. First, defensin 1 genes of A. cerana and A. dorsata were sequenced, after which a bioinformatic analysis was conducted. The amplified length of these defensin 1 genes of A. cerana and A. dorsata were 479 and 458 bp, respectively, and their putative amino acid sequences comprised 66 and 65 amino acids, respectively, with 6 cysteine residues. The cysteine residues formed a disulfide bond and then linked the three domains in the defensin peptide with each other, thereby allowing the lysis of the bacterial membrane through pore formation. Intron 2 of the defensin gene demonstrated nucleotide variations between A. cerana from Indonesia and that from Korea and between A. dorsata from Indonesia and that from Malaysia; the latter species also demonstrated variations in exon 3. Phylogenetic tree topology of the bee, which was constructed based on defensin 1 gene, was compatible with a previous study showing that A. cerana and A. dorsata are more closely related to A. mellifera than to A. florea.